TraduXio Project: Latest Upgrades and Feedback - Lacour, Philippe; Bénel, Aurélien (Journal of data mining and digital humanities, 2021)
TraduXio is a digital environment for computer assisted multilingual translation which is web-based, free to use and with an open source code. Its originality is threefold-whereas traditional technologies are limited to two languages (source/target), TraduXio enables the comparison of different versions of the same text in various languages; its concordancer provides relevant and multilingual suggestions through a classification of the source according to the history, genre and author; it uses collaborative devices (privilege management, forums, networks, history of modification, etc.) to promote collective (and distributed) translation. TraduXio is designed to encourage the diversification of language learning and to promote a reappraisal of translation as a professional skill. It can be used in many different ways, by very diverse kind of people. In this presentation, I will present the recent developments of the software (its version 2.1) and illustrate how specific groups (language teaching, social sciences, literature) use it on a regular basis. In this paper, I present the technology but concentrate more on the possible uses of TraduXio, thus focusing on translators' feedback about their experience when working in this digital environment in a truly collaborative way.